DELAYED MANAGEMENT OF BILATERAL MASSIVE EPIDURAL HEMATOMA INVOLVING PARASAGITTAL SINUS: A COMPREHENSIVE SCOPING REVIEW FROM INDONESIAN PERSPECTIVES - Suryaningtyas, Wihasto; Armando, Alivery Raihanada; Ramadhan, Candra Dwantara; Kamaruddin, Muhammad Fadhil; Zamzam, Ramadhani Rizki; Nathania, Nathania (Folia Medica Indonesiana, 2025)
Introduction: Vertex epidural hematomas (VEDH) involving the superior sagittal sinus (SSS) are rare, critical injuries often complicated by massive venous hemorrhage. This study evaluates the clinical outcomes of VEDH and identifies systemic barriers contributing to treatment delays in Low- and Middle-Income Countries (LMICs). Methods: We present a case series of three patients managed at an Indonesian tertiary center alongside a scoping review of 33 studies. Delayed management was defined as prolonged injury-to-surgery intervals resulting from referral inefficiencies and transport logistics. Results: The series highlights a unique case of a 66-year-old male with bilateral VEDH and SSS laceration who underwent surgery 32 hours post-injury. Despite massive intraoperative blood loss (6000cc) requiring aggressive transfusion and sinus repair, the patient achieved a good functional recovery. The scoping review identified primary barriers to timely care, including geographical constraints, lack of organized emergency transport, and a scarcity of neurosurgical specialists and CT scanners in rural regions. Conclusion: While delayed presentation exacerbates surgical risks, aggressive management via bicoronal craniotomy remains effective. Improving prehospital infrastructure and referral networks is essential to reducing preventable delays in neurotrauma management.